Gamification of risk management learning material in the ESF-funded Kompassi project : report on case “Riskivirasto” - Mäenpää, Mikael (Vaasan yliopisto, 2024)
The Kompassi project, funded by the European Social Fund (ESF) and coordinated by the University of Vaasa, aimed to improve through a digital learning environment the competencies of Finnish South Ostrobothnian companies and unemployed young adults under the age of 25. One of the main activities of the project was to create a digital learning game focused on digital risk management skills to stimulate learning and interest in this important area of competence. The Riskivirasto (“Risk Agency”) learning game, which was brainstormed during a storytelling workshop in Seinäjoki, Finland, utilised a wide range of skills and ideas from the participants. The purpose of this report is to provide a perspective on the process of how gamified solutions can be used to support the goals of educational projects. This report describes the whole gamification design process and the results of related tests, surveys and statistics on the implemented learning game. Overall, the project succeeded in creating a gamified learning environment, emphasised collaboration and involvement of the target group, and contributed to the understanding of effective gamification in education. This report has been written with the intent for giving input to future European Social Fund projects involving online learning environments and gamification.
Keywords: gamification; digital games; risk management; educational games; game design; computer games; online learning; planning and design; games; fi=Tuotantotalous|en=Industrial Management|